Examining Transparency, Due Diligence, and Digital Inclusion as Resilient Values for Provenance Research Work. Issue 1 (14th October 2022) - Buchanan, Sarah; Bartley, Jane; Bennett, Danielle; Campbell, Elizabeth; Niu, Jinfang; Reed, Victoria
ABSTRACT: In response to the rising calls for transparency in displaying collections information, an ongoing research project is developing and studying provenance research methods in four domains, which cross museum and archive settings and their legal oversight in the United States: art collections (furthermore colonial era and Nazi‐looted era), special collections and manuscripts, Native and Indigenous research, and local or rural history collections. We illustrate three resilient values underpinning successful or at least informative provenance research: transparency, due diligence, and digital inclusion. Together the values, when practiced further, will guide information professionals towards researching collections provenance more effectively according to internal and public‐facing goals.